IMPROVING THE ECONOMIC EFFICIENCY OF CLOTHING MANUFACTURING ENTERPRISES IN UZBEKISTAN - Akhmedova Gaziza Azimkyzy (Innovate Conferences, 2025)
This study is dedicated to the issues of enhancing the economic efficiency of clothing manufacturing enterprises in Uzbekistan. The paper analyzes the key factors influencing the competitiveness and profitability of textile enterprises in the republic under modern market conditions.